Therapeutic potential of zinc 64Zn aspartate for obesity management: impact on oxidative stress, lipid metabolism, pancreas and liver in high-calorie diet model - Temnik, Max; Gurin, Sergey; Balakin, Alexandr; Byshovets, Roman; Kalmukova, Olesia; Vovk, Tetiana; Halenova, Tetiana; Raksha, Nataliia; Falalyeyeva, Tetyana; Savchuk, Olexiy (Frontiers in Pharmacology, 2025)
Zinc is a critical micronutrient that plays multifaceted roles in oxidative stress management, lipid metabolism, pancreatic function, and liver health, which are all closely interconnected with obesity. Maintaining adequate zinc levels is essential for overall metabolic health and proper functioning of these vital systems. The investigational new drug complex of zinc-64 aspartate (KLS-1 or 64Zn-aspartate) was evaluated in this study as a pharmaceutical agent targeting oxidative stress and lipid metabolism using rodent model of obesity. KLS-1 is the isotopically modified zinc aspartate in which stable (non-radioactive) 64Zn atoms were enriched to exceed 99% atomic fraction of total zinc, as compared to natural isotopic ratio of 64Zn of 48.6%. In this paper, we discuss our findings and the effects rendered by KLS-1 on lipid metabolism, pancreas and liver function. This study was conducted on outbred rats, which were divided into four experimental groups: 1) the control group consuming standard food (3.81 kcal/g), 2) the obese group consuming a high-calorie diet (5.35 kcal/g), 3) the obese group consuming a high-calorie diet (5.35 kcal/g) treated with intragastric administration of 64Zn- aspartate at a dose of 4.5 mg per animal during 6 weeks (the obese rats), 4) the group consuming standard food diet (3.81 kcal/g) with 64Zn- aspartate form administration. The obese rats treated with 64Zn-64 stable isotope demonstrated decreased area of the hepatocytes, insulin and glucose levels in serum; increased catalase and superoxide dismutase activity, and area of pancreatic islets in comparison with the obese group. The study shows that 64Zn-aspartate is effective as a therapeutic agent for obesity management, significantly reducing body mass, improving histopathological changes in the pancreas and liver and normalizing oxidative stress in high-calorie diet animal models. These findings suggest that 64Zn- aspartate may be a promising monotherapy or adjunct treatment for obesity, offering benefits in weight reduction, organ protection, and antioxidant balance.